Investigation of College Students' Online Learning - Zheng, Jianyun; Huang, Yongtao; Li, Shilian; Wang, Changtao; Zhong, Kangjia (2020 International Conference on Big Data and Informatization Education (ICBDIE), 2020)
With the development of various online teaching platforms, various online courses are provided for learners. Especially this year, novel coronavirus pneumonia has occurred. Colleges and universities have adopted online courses for teaching. This survey is based on the analysis of College Students' learning situation of online courses and how to improve the effect of online courses learning.